A new mixed time-frequency simulation method for nonlinear heterogeneous multirate RF Circuits - Oliveira, Jorge dos Santos Freitas de (2011)
This paper describes a new mixed time-frequency method especially conceived for the efficient simulation of nonlinear multirate RF circuits evidencing some heterogeneity. The proposed method splits the circuit into two subsets, and can be seen as a hybrid scheme combining the popular envelope transient harmonic balance (ETHB) technique with a purely time-marching engine. With this method, the hardest nonlinearities of the circuit are appropriately computed in a strictly time-domain approach, whereas the more moderate ones are processed in the frequency-domain. Simulation tests are performed with an illustrative circuit example, revealing gains in computation speed of more than one order of magnitude over mature ETHB.